2020
DOI: 10.3389/fgene.2020.00347
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation and Hydroxymethylation in Cervical Cancer: Diagnosis, Prognosis and Treatment

Abstract: Recent discoveries have led to the development of novel ideas and techniques that have helped elucidate the correlation between epigenetics and tumor biology. Nowadays, the field of tumor genetics has evolved to include a new type of regulation by epigenetics. An increasing number of studies have demonstrated the importance of DNA methylation and hydroxymethylation in specific genes in the progression of cervical cancer. Determining the methylation and hydroxymethylation profiles of these genes will help in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 88 publications
1
33
0
Order By: Relevance
“…Epigenetic modification of DNA refers to a chemical modification process in which a methyl group is transferred to a cytosine, most commonly at a CpG (cytosine linked to guanine by a phosphate group, cytosine-phospho-guanine, 5′-C-p-G-3′) site [ 11 ]. DNA methylation without base sequence alteration is considered as the most common and highly dynamic epigenetic modification, which is the result of the function of cytosine DNA methyltransferases (DNMTs) [ 12 , 13 ]. DNMTs contain three members: DNA methyltransferase 1 (DNMT1), DNA methyltransferase 3a (DNMT3a), and DNA methyltransferase 3b (DNMT3b).…”
Section: Epigenetic Modification Expression Profile In Keloidmentioning
confidence: 99%
“…Epigenetic modification of DNA refers to a chemical modification process in which a methyl group is transferred to a cytosine, most commonly at a CpG (cytosine linked to guanine by a phosphate group, cytosine-phospho-guanine, 5′-C-p-G-3′) site [ 11 ]. DNA methylation without base sequence alteration is considered as the most common and highly dynamic epigenetic modification, which is the result of the function of cytosine DNA methyltransferases (DNMTs) [ 12 , 13 ]. DNMTs contain three members: DNA methyltransferase 1 (DNMT1), DNA methyltransferase 3a (DNMT3a), and DNA methyltransferase 3b (DNMT3b).…”
Section: Epigenetic Modification Expression Profile In Keloidmentioning
confidence: 99%
“…The low specificity (31%) and positive predictive value (37%) even make the situation worse because they lead to more patients undergoing unnecessary referrals 37 . Recent studies have shown the correlation between epigenetics and development and progression of cervical cancer 41 . Increased methylation of host genes has been observed in women with cervical precancer and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the mortality rates are still high [27]. Nowadays, an increasing number of studies have demonstrated the importance of a new type of regulation by epigenetics in speci c genes in the progression of cervical cancer [29]. This provides new ideas for the treatment of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%